Shifting Horizons of Public International Law A South Asian Perspective (Springer India, 2018)
This book offers a South Asian perspective on international law, maintaining a suitable distance from the 'Western' approach. The themes discussed reflect the region's particular contribution to the development of international law. Each South Asian country has its own important role to play in promoting regional trade, regulating maritime affairs, ensuring access to water, debating State responsibility, engaging with International Criminal Court, questioning diplomatic and consular immunities, and, most importantly, upholding human rights. These issues are addressed by local contributors from Nepal, Bangladesh and Sri Lanka, who have come together to represent the whole South Asian region on a single academic platform.